Microbial dynamics of antibiotic resistance. (Research'eu results magazine)
Microbial antibiotic resistance develops in the gut through the selection of pre-existing resistant bacteria and gene transfer events. Scientists investigated the dynamics of the entire collection of 'Antimicrobial resistance determinants' (ARDs), also known as the resistome, in the human gut.